Perlindungan Investor Dalam Mendorong Kemajuan Investasi Startup di Indonesia Melalui Pengembalian Keuntungan Tidak Sah - Arthaleza, Fergie Brillian; Dirkareshza, Rianda (Jurnal Locus Penelitian dan Pengabdian, 2025)
The startup ecosystem in Indonesia is currently facing serious challenges in terms of funding, triggered by declining investment flows and weak legal protections for investors in the capital market. This condition has an impact on the declining level of investor confidence and investment readiness of startups, especially in the initial and intermediate funding stages. This study aims to examine the role of the Financial Services Authority (OJK) through OJK Regulation Number 65/POJK.04/2020 in strengthening investor protection and assess its implications for increasing the investment readiness of startups in Indonesia. The research method used is normative juridical with a statutory approach, a case approach, and a conceptual approach. The analysis focused on the relationship between the mechanism for the return of unauthorized profits (disgorgement), the establishment of an investor loss compensation fund, and the remedial authority of the OJK in enforcing capital market laws. The results of the study show that the regulation of disgorgement and other investor protection instruments is able to increase legal certainty, transparency, and accountability of startup governance, thereby encouraging regulatory compliance discipline. This mechanism provides a guarantee of loss recovery for investors and has a positive impact on increasing investor confidence. However, its implementation still faces challenges, especially related to the limited supervisory capacity and complexity of the startup's digital business model. Thus, POJK No. 65/POJK.04/2020 not only functions as an instrument to protect investors, but also has a strategic role in strengthening investment readiness and creating a safer, credible, and sustainable startup investment climate.